Fluidized bed method-based silicon-carbon negative electrode active material and preparation method thereof

By uniformly covering the silicon-carbon anode material of the MoxOyPz layer on the silicon-carbon surface, the problem of incompatibility of silicon-carbon composite materials and sulfide solid electrolytes in sulfide all-solid state batteries is solved, and the rate performance and cycling performance of the battery are significantly improved.

CN119627064APending Publication Date: 2025-03-14GAO NENG SHI DAI (SHEN ZHEN) XIN NENG YUAN KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411600957.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials are difficult to use in sulfide all-solid state batteries because the sulfide solid electrolyte is incompatible with carbon materials, resulting in poor battery rate performance and cycling performance.

Method used

A silicon carbon negative electrode active material prepared based on the fluidized bed method is used. This material consists of silicon carbon and MoxOyPz layers, which are uniformly coated on the surface of silicon carbon, and a material with excellent structural stability is obtained by high temperature calcination.

Benefits of technology

This material significantly improves the rate performance and cycling performance in all-solid-state batteries, effectively prevents the direct contact between the sulfide solid electrolyte and the silicon carbon negative electrode, inhibits the generation of high-resistance substances, and maintains the integrity and stability of the structure of the material and electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627064A_ABST
    Figure CN119627064A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and particularly discloses a silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof. Comprising silicon carbon and a Mo < x > O < y > P < z > layer; the Mo < x > O < y > P < z > layer coats the silicon carbon; wherein 0 < x < 1, 0 < y < 1.6, and 0 < z < 1. The silicon-carbon negative electrode active material prepared by the invention has excellent cycling stability and rate capability, and the MoxOyPz with excellent structural stability is uniformly coated on the silicon-carbon surface, so that direct contact between sulfide solid electrolyte and a silicon-carbon negative electrode can be effectively prevented, generation of high-resistance substances is inhibited, and increase of battery polarization and deterioration of rate are avoided; li < + > can be received in the first lithiation process to form a rapid transmission channel, and Li < + > transmission is accelerated; due to the excellent structural stability of MoxOyPz, the MoxOyPz can bear volume expansion and shrinkage in the silicon-carbon lithiation lithium removal process, so that the material and the electrode keep complete and stable in structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof. Background Art

[0002] The booming new energy vehicle market has led to a sharp increase in demand for high-performance lithium-ion batteries. The performance and market acceptance of new energy vehicles largely depend on the performance of lithium-ion batteries, including energy density, safety, cycle stability, cost, and charge rate. At present, all-solid-state batteries have become the goal pursued by the lithium battery industry due to their extremely high energy density and ultra-high safety. Among them, sulfide all-solid-state batteries have become a hot topic of concern due to their higher energy density, ultra-high safety, and easier implementation. The negative electrode material determines the energy density of sulfide all-solid-state batteries. Silicon-based negative electrodes (Si, Si / C, SiO x and SiO2) have been widely studied due to their ultra-high theoretical specific capacity (4200mAh / g), suitable operating voltage, abundant resources and other advantages. Silicon-based negative electrodes have been gradually applied to lithium-ion batteries, and their penetration rate in the field of lithium-ion battery negative electrodes has gradually increased.

[0003] However, the silicon-based negative electrode will produce a huge intrinsic volume expansion of 180-400% during the lithiation process, which will cause the active material to fall off and pulverize on the current collector, causing the capacity of the silicon-based negative electrode to decay rapidly. At present, a variety of strategies have been developed to inhibit the volume expansion of silicon-based negative electrodes, including nano-sizing, porosification, surface coating, silicon-carbon composites, and composites with other materials. Among them, the third-generation silicon-carbon negative electrode material prepared by fluidized bed can achieve a volume expansion of <100%, which can be used in liquid lithium-ion batteries.

[0004] However, the silicon-carbon composite materials currently used in liquid batteries are difficult to apply to sulfide all-solid-state batteries because sulfide solid electrolytes are incompatible with carbon materials, and carbon materials will accelerate the decomposition of sulfide solid electrolytes. Therefore, finding new composite materials is an important development direction for silicon-based negative electrodes of sulfide all-solid-state batteries.

[0005] Therefore, it is necessary to provide a silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof, so as to improve the rate performance and cycle performance of all-solid-state batteries. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof, so as to improve the rate performance and cycle performance of an all-solid-state battery.

[0007] A first aspect of the present invention provides a silicon-carbon negative electrode active material based on a fluidized bed method.

[0008] Specifically, silicon carbon and Mo x O y P z layer;

[0009] The Mo x O y P z A layer covers the silicon carbon;

[0010] Among them, 0<x<1, 0<y<1.6, 0<z<1.

[0011] Preferably, 0.5<x<1, 0<y<1.6, 0.4<z<1.

[0012] Preferably, the D of the silicon-carbon negative electrode active material 50 The surface area is 8-30 μm and the specific surface area is 1.2-5.4 m 2 / g.

[0013] Further preferably, the D of the silicon-carbon negative electrode active material 50 The surface area is 8 to 20 μm and the specific surface area is 2 to 5 m 2 / g.

[0014] More preferably, the silicon-carbon negative electrode active material has a D 50 The surface area is 9 to 12 μm and the specific surface area is 2 to 4 m 2 / g.

[0015] Preferably, the silicon carbon D 50 The thickness is 7 to 20 μm, and the reversible capacity is 1600 to 2200 mAh / g.

[0016] Further preferably, the silicon carbon D 50 The thickness is 8 to 15 μm, and the reversible capacity is 1800 to 2200 mAh / g.

[0017] More preferably, the silicon carbon D 50 The thickness is 8 to 10 μm, and the reversible capacity is 1800 to 2000 mAh / g.

[0018] Preferably, the silicon carbon includes third-generation silicon carbon materials.

[0019] A second aspect of the present invention provides a method for preparing a silicon-carbon negative electrode active material.

[0020] Specifically, the following steps are included:

[0021] (1) placing silicon carbon inside a fluidized bed, filling it with protective gas, and then opening the fluidized bed to allow the silicon carbon to float inside the fluidized bed;

[0022] (2) dissolving a molybdenum source in a solvent to obtain a molybdenum source solution, and controlling the speed of a peristaltic pump to add the molybdenum source solution into the fluidized bed and coat the silicon carbon;

[0023] (3) controlling the temperature in the fluidized bed chamber, heating up the gasified phosphorus source and pumping it into the fluidized bed for deposition to obtain a semi-finished material;

[0024] (4) The semi-finished material is taken out and calcined at high temperature to obtain the silicon-carbon negative electrode active material.

[0025] Preferably, in step (1), the parameters for starting the fluidized bed include: the fan air volume is 100 to 200 m 3 / h, turntable speed is 100-200rpm, inlet air temperature is 50-100℃, and material temperature is 50-100℃.

[0026] Further preferably, in step (1), the parameters for starting the fluidized bed include: the fan air volume is 150 to 200 m 3 / h, turntable speed is 150-200rpm, inlet air temperature is 50-80℃, and material temperature is 50-80℃.

[0027] More preferably, in step (1), the parameters for starting the fluidized bed include: the fan air volume is 150m 3 / h, turntable speed is 150rpm, inlet air temperature is 70℃, and material temperature is 60℃.

[0028] Preferably, in step (2), the solvent includes at least one of water, ethanol, dimethyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, and methyl tert-butyl ether.

[0029] Preferably, in step (2), the rotation speed of the peristaltic pump is 1 to 10 rpm.

[0030] Further preferably, in step (2), the rotation speed of the peristaltic pump is 1 to 5 rpm.

[0031] More preferably, in step (2), the rotation speed of the peristaltic pump is 4 rpm.

[0032] Preferably, in step (2), the molybdenum source includes at least one of ammonium molybdate, sodium molybdate, iron molybdate, and dodecamolybdate heteropolyacid salt.

[0033] Further preferably, the dodecamolybdate heteropolyacid salt includes at least one of sodium phosphomolybdate and ammonium phosphomolybdate.

[0034] Preferably, in step (3), the phosphorus source includes at least one of red phosphorus, white phosphorus, black phosphorus and sodium hypophosphite.

[0035] Preferably, the mass ratio of the silicon carbon, the molybdenum source and the phosphorus source is 200:(1-5):(1-4).

[0036] Further preferably, the mass ratio of the silicon carbon, the molybdenum source and the phosphorus source is 200:(1-4):(1-4).

[0037] More preferably, the mass ratio of the silicon carbon, the molybdenum source and the phosphorus source is 200:(1-4):(1-3).

[0038] Preferably, in step (2), the molybdenum source is in the form of a solution with a solution concentration of 0.05 to 1 mol / L.

[0039] Further preferably, in step (2), the molybdenum source is in the form of a solution with a solution concentration of 0.1 to 0.5 mol / L.

[0040] More preferably, in step (2), the molybdenum source is in the form of a solution with a solution concentration of 0.158 mol / L.

[0041] Preferably, in step (3), the temperature in the chamber is 200-350° C. and maintained for 1-20 hours.

[0042] Further preferably, in step (3), the temperature in the chamber is 280-350° C. and maintained for 1-10 hours.

[0043] More preferably, in step (3), the temperature in the chamber is 290° C. and is maintained for 1 hour.

[0044] Preferably, in step (4), the high temperature calcination is carried out at a temperature of 500 to 800° C. and for a time of 2 to 12 hours.

[0045] Further preferably, in step (4), the high temperature calcination is carried out at a temperature of 600 to 800° C. and for a time of 2 to 5 hours.

[0046] More preferably, in step (4), the high temperature calcination is carried out at a temperature of 600° C. and for a time of 2 h.

[0047] Preferably, in step (1), the protective gas includes at least one of argon and nitrogen.

[0048] A third aspect of the present invention provides a negative electrode.

[0049] Specifically, the negative electrode includes the silicon-carbon negative electrode active material provided in the first aspect.

[0050] A fourth aspect of the present invention provides an all-solid-state lithium-ion battery.

[0051] Specifically, the all-solid-state lithium-ion battery includes the negative electrode provided by the third aspect.

[0052] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0053] The silicon-carbon negative electrode active material prepared by the present invention has excellent cycle stability and rate performance. A layer of material containing molybdenum and phosphorus is uniformly coated on the surface of silicon-carbon based on a fluidized bed, and Mo with excellent structural stability is obtained by high-temperature calcination. x O y P z , which is evenly coated on the silicon-carbon surface, can effectively prevent the direct contact between the sulfide solid electrolyte and the silicon-carbon negative electrode, inhibit the generation of high-resistance materials, avoid the increase of battery polarization and the deterioration of the rate; and it can receive Li during the first lithiation process + Form a fast transmission channel to accelerate Li + Transmission; thanks to Mo x O y P z The excellent structural stability can withstand the volume expansion and contraction during the silicon-carbon lithiation and delithiation process, thereby maintaining the integrity and stability of the material and electrode structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 The figure is a test result of the rate performance of the all-solid-state lithium-ion battery composed of the silicon-carbon negative electrode active material of Example 1 and Comparative Example 3;

[0055] Figure 2 This is a graph showing the results of scanning electron microscopy testing and energy dispersive X-ray spectroscopy testing in Example 1. DETAILED DESCRIPTION

[0056] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0057] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0058] Example 1

[0059] A silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof.

[0060] Silicon-carbon negative electrode active material: Silicon-carbon and Mo 0.79 O 0.92 P 0.65 Layer composition; Mo 0.79 O 0.92 P 0.65 Layer coated with silicon carbon, wherein silicon carbon D 50=9.21μm, reversible capacity 1910.7mAh / g.

[0061] The specific preparation method is as follows:

[0062] (1) Place 200g of silicon carbon inside the fluidized bed, seal the inner chamber, and fill it with argon to replace the internal air. Turn on the fluidized bed and set the fan air volume to 150m 3 / h, the rotating disk speed is 150rpm, the inlet air temperature is 70℃, and the material temperature is 60℃, so that the silicon carbon floats inside the fluidized bed;

[0063] (2) Dissolve 2.796 g of ammonium molybdate tetrahydrate in 100 g of deionized water (the concentration of molybdenum atoms is 0.158 mol / L), stir to dissolve, control the speed of the peristaltic pump to 4 rpm, pump the molybdenum source solution into the fluidized bed cavity and coat the silicon carbon;

[0064] (3) Changing the internal temperature of the fluidized bed cavity to 290° C. and the inlet air temperature to 450° C., heating 2 g of red phosphorus to 450° C. to sublimate into gas, slowly injecting the gaseous red phosphorus into the fluidized bed cavity, maintaining the deposition for 1 hour, and then gradually cooling down to obtain a semi-finished material;

[0065] (4) Finally, the semi-finished material is taken out and calcined in an argon environment at a high temperature of 600°C for 2 hours to obtain a silicon-carbon negative electrode active material.

[0066] Example 2

[0067] A silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof.

[0068] Silicon-carbon negative electrode active material: Silicon-carbon and Mo 0.95 O 1.40 P 0.65 Layer composition; Mo 0.95 O 1.40 P 0.65 Layer coated with silicon carbon, wherein silicon carbon D 50 =9.21μm, reversible capacity 1910.7mAh / g.

[0069] The difference from Example 1 is that the mass of ammonium molybdate tetrahydrate in Example 2 is 3.355 g. The preparation method is the same as that in Example 1.

[0070] Example 3

[0071] A silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof.

[0072] Silicon-carbon negative electrode active material: Silicon-carbon and Mo 0.63 O 0.45 P 0.65 Layer composition; Mo 0.63 O0.45 P 0.65 Layer coated with silicon carbon, wherein silicon carbon D 50 =9.21μm, reversible capacity 1910.7mAh / g.

[0073] The difference from Example 1 is that the mass of ammonium molybdate tetrahydrate in Example 3 is 2.237 g. The preparation method is the same as that in Example 1.

[0074] Example 4

[0075] A silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof.

[0076] Silicon-carbon negative electrode active material: Silicon-carbon and Mo 0.79 O 0.20 P 0.97 Layer composition; Mo 0.79 O 0.20 P 0.97 Layer coated with silicon carbon, wherein silicon carbon D 50 =9.21μm, reversible capacity 1910.7mAh / g.

[0077] The difference from Example 1 is that the mass of red phosphorus in Example 4 is 3.0 g. The preparation method is the same as that in Example 1.

[0078] Example 5

[0079] A silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof.

[0080] Silicon-carbon negative electrode active material: Silicon-carbon and Mo 0.79 O 1.29 P 0.48 Layer composition; Mo 0.79 O 1.29 P 0.48 Layer coated with silicon carbon, wherein silicon carbon D 50 =9.21μm, reversible capacity 1910.7mAh / g.

[0081] The difference from Example 1 is that the mass of red phosphorus in Example 5 is 1.5 g. The preparation method is the same as that in Example 1.

[0082] Comparative Example 1

[0083] A silicon-carbon negative electrode active material and a preparation method thereof.

[0084] Silicon-carbon negative electrode active material: Silicon-carbon and Mo 0.79 O 2.38 P 3.23 Layer composition; Mo 0.79 O 2.38 P 3.23Layer coated with silicon carbon, wherein silicon carbon D 50 =9.21μm, reversible capacity 1910.7mAh / g.

[0085] The specific preparation method is as follows:

[0086] 200 g of silicon carbon, 2.796 g of ammonium molybdate tetrahydrate, and 2.0 g of red phosphorus were ball-milled at 500 rpm for 1 h, and then the sample was calcined at 600° C. in an argon environment for 2 h to obtain a silicon carbon negative electrode active material.

[0087] Comparative Example 2

[0088] A silicon-carbon negative electrode active material based on a fluidized bed method and a preparation method thereof.

[0089] Silicon-carbon negative electrode active material: Silicon-carbon and Mo 0.79 O 2.38 P 6.46 Layer composition; Mo 0.79 O 2.38 P 6.46 Layer coated with silicon carbon, wherein silicon carbon D 50 =9.21μm, reversible capacity 1910.7mAh / g.

[0090] The difference from Example 1 is that the mass of red phosphorus in Comparative Example 2 is 5 g. The preparation method is the same as that of Example 1.

[0091] Comparative Example 3

[0092] A silicon-carbon negative electrode active material and a preparation method thereof.

[0093] Silicon-carbon negative electrode active material: directly composed of the silicon-carbon in Example 1, without including a coating layer.

[0094] 1. Characterization of physical and chemical properties of materials.

[0095] The silicon-carbon negative electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 3 were tested by a Malvern laser particle size analyzer to obtain the median particle size D of the materials. 50 , and the Brunauer-Emmett-Teller (BET) test was performed to obtain the specific surface area of ​​the material. The test results are shown in Table 1.

[0096] Table 1 Median particle size and specific surface area of ​​each silicon-carbon negative electrode active material

[0097]

[0098]

[0099] 2. Microscopic morphology characterization.

[0100] Scanning electron microscope (SEM) test and energy dispersive X-ray spectroscopy (EDS) test were performed on Example 1, and the results are as follows: Figure 2 The Mo and P elements are evenly distributed on the surface of the silicon-carbon material, indicating that Example 1 achieves uniform Mo on the surface of the silicon-carbon material. x O y P z Coating. The surface is evenly coated with Mo x O y P z It can effectively improve the interfacial contact between silicon carbon and sulfide solid electrolyte, and form a fast lithium ion conductor during the first lithium insertion process, thereby achieving excellent rate performance.

[0101] 3. Electrochemical performance test.

[0102] The silicon-carbon negative electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 3 were mixed with LiP6S5Cl, vapor-grown carbon fiber (VGCF), and polytetrafluoroethylene (PTFE) in a mass ratio of 60:37:2:1 to form a composite negative electrode, and a negative electrode sheet of suitable size was obtained through a roller pressing and slicing process. The negative electrode sheet was then placed in a polyetheretherketone tube with a diameter of 10 mm, and then 100 mg of LiP6S5Cl was weighed and added to the tube. The tube was pressed and molded at a pressure of 30 MPa and tightly contacted with the negative electrode sheet. Finally, an indium sheet and a lithium sheet were added to the other side of the solid electrolyte, and the tube was pressed and molded at a pressure of 4 tons to prepare an all-solid-state lithium-ion battery with a three-layer structure (composite negative electrode / solid electrolyte / Li-In alloy).

[0103] (1) Cycle performance test conditions: At 60°C, the first and second cycles were activated with a current of 0.1C, followed by a cycle test with a current of 0.5C, the test cut-off voltage was -0.61 to 0.9V, and the battery was tested under a pressure of 25MPa. The test method for the first cycle discharge specific capacity is: the first cycle constant current discharge is performed at 60°C with a current of 0.1C; the calculation formula for the 50-cycle specific capacity retention rate (%) is: 50-cycle specific capacity retention rate = (50th cycle discharge specific capacity / 3rd cycle discharge specific capacity) × 100%, and the results are shown in Table 2.

[0104] Table 2: Cyclic performance results of all-solid-state lithium-ion batteries composed of Examples 1 to 5 and Comparative Examples 1 to 3

[0105]

[0106]

[0107] The all-solid-state lithium-ion battery composed of Example 1 exhibits the best cycle stability, with a first cycle specific capacity of 2018.75 mAh / g, and a capacity retention rate of 96.23% after 50 cycles at 0.5C. The all-solid-state lithium-ion batteries composed of Examples 2 to 5 also exhibit excellent cycle stability, with a 50-cycle specific capacity retention rate of more than 95%. On the contrary, the all-solid-state lithium-ion batteries composed of Comparative Examples 1 to 3 exhibit poor cycle stability and are difficult to meet practical application requirements.

[0108] (2) Rate performance test conditions: 0.1C current activation was performed at 60°C for the first and second cycles, followed by 5 cycles at 0.5C, 0.8C, 1C, and 2C respectively. The test cutoff potential was -0.61 to 0.9V, and the battery was tested at a pressure of 25MPa.

[0109] The rate performance tests of the all-solid-state lithium-ion batteries of Example 1 and Comparative Example 3 were performed respectively, and the results are as follows: Figure 1 Sample 1 exhibits excellent rate performance, which is attributed to the Mo coated on its surface. x O y P z The layer effectively inhibits the degradation and decomposition of the sulfide solid electrolyte in the silicon-carbon negative electrode material, and the Mo after lithium insertion x O y P z It has high ionic conductivity and effectively stabilizes the Li + transmission, which is beneficial to Li + Fast transmission to achieve high rate performance and cycle stability.

[0110] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.

Claims

1. A silicon-carbon negative electrode active material based on a fluidized bed method, characterized in that: Including silicon carbon and Mo x O y P z layer; The Mo x O y P z A layer covers the silicon carbon; Among them, 0<x<1, 0<y<1.6, 0<z<1.

2. The silicon-carbon negative electrode active material according to claim 1, characterized in that: The silicon-carbon negative electrode active material D 50 The surface area is 8-30 μm and the specific surface area is 1.2-5.4 m 2 / g.

3. The silicon-carbon negative electrode active material according to claim 1, characterized in that: The silicon carbon D 50 The thickness is 7 to 20 μm, and the reversible capacity is 1600 to 2200 mAh / g.

4. The method for preparing the silicon-carbon negative electrode active material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) placing silicon carbon inside a fluidized bed, filling it with protective gas, and then opening the fluidized bed to allow the silicon carbon to float inside the fluidized bed; (2) dissolving a molybdenum source in a solvent to obtain a molybdenum source solution, and controlling the speed of a peristaltic pump to add the molybdenum source solution into the fluidized bed and coat the silicon carbon; (3) controlling the temperature in the fluidized bed chamber, heating up the gasified phosphorus source and pumping it into the fluidized bed for deposition to obtain a semi-finished material; (4) The semi-finished material is taken out and calcined at high temperature to obtain the silicon-carbon negative electrode active material.

5. The preparation method according to claim 4, characterized in that: In step (2), the molybdenum source includes at least one of ammonium molybdate, sodium molybdate, iron molybdate, and dodecamolybdate heteropolyacid salt.

6. The preparation method according to claim 4, characterized in that: In step (3), the phosphorus source includes at least one of red phosphorus, white phosphorus, black phosphorus, and sodium hypophosphite.

7. The preparation method according to claim 4, characterized in that: The mass ratio of the silicon carbon, the molybdenum source and the phosphorus source is 200:(1-5):(1-10).

8. The preparation method according to claim 4, characterized in that: In step (2), the molybdenum source is in the form of a solution with a concentration of 0.05 to 1 mol / L.

9. A negative electrode, characterized in that The negative electrode comprises the silicon-carbon negative electrode active material according to any one of claims 1 to 3.

10. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the negative electrode according to claim 9.